THE NEWS CONSTRUCTION OF "TGB EFFECT" BASED ON DISCOURSE ANALYSIS OF TEUN A. VAN DJIK ON DAILY NEWS OF LOMBOK POST AND SUARA NTB - Zdatunnithaqain; Winengan; Faizah (Wasilatuna: Jurnal Komunikasi dan Penyiaran Islam, 2025)
In news reporting, it cannot be separated from the reporting process of events, writing, selecting of information, and the publish of news results through mass media.The news event depiction is related to the representation of the event construction as reality built by journalists through written language by containing words, images, sentences,metaphors,language styles,and others.Newspapers through the discourse built are able to provide a choice whether something displayed is goodor not in society. The TGB effect was an issue raised and published on local media which showed TGB's move to the Perindo Party which indirectly has an impact on a number of politiciansfromvariouspoliticalparties.Thetitleofthisresearchis"News Constructionof "TGBEffect"BasedonDiscourse Analysisof Teun A. VanDjikon DailyNewsofLombokPostandSuaraNTB"withafocusonthereporting construction of TGB Effect by using the Van Djik model, this type of research used qualitative research by using a critical paradigm approach. The finding of data through news texts related to the TGB effect, the data collection through unstructured interviews, and documentation. The results of this research showed that the reporting of the TGB effect in theTeun A. Van Djik model contained three elements: First, the text. In this element, there weredifferencesinthechoiceofnewstitleswithcontentswhichwerenotmuch different. Second, the social cognition, both media used the schemas of role, person, and event. While social analysis contained the power practice and accessed to influence discourses. Keywords:Discourseanalysis,TGBeffect,LombokPost,SuaraNTB